2014
DOI: 10.1016/j.mineng.2013.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of steel slag by a combined carbonation and granulation treatment

Abstract: This work reports the results of a combined accelerated carbonation and wet granulation treatment applied to Basic Oxygen Furnace (BOF) steel slag with the aim of producing secondary aggregates for civil engineering applications and of storing CO2 in a solid and thermodynamically stable form. The tests were carried out in a laboratory scale granulation device equipped with a lid and CO2 feeding system. In each test, humidified slag (liquid/solid ratio of 0.12 l/kg) was treated for reaction times varying betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
43
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 30 publications
5
43
2
Order By: Relevance
“…Ca, K, Mg, and Na release decreased compared to the fresh slag, in accordance with the pH values measured after the treatment. In particular, the decrease in the Ca concentration, from 1500 mg/L to around 700 mg/L (for Z3) and 800 mg/L (for Z1 and Z2), was linked to the formation of CaCO 3 , less soluble than CaO and Ca(OH) 2 , in accordance to what reported in our previous study and with the results of Morone et al , where Ca concentrations in the eluates decreased of at least one order of magnitude compared to the untreated material.…”
Section: Resultssupporting
confidence: 92%
“…Ca, K, Mg, and Na release decreased compared to the fresh slag, in accordance with the pH values measured after the treatment. In particular, the decrease in the Ca concentration, from 1500 mg/L to around 700 mg/L (for Z3) and 800 mg/L (for Z1 and Z2), was linked to the formation of CaCO 3 , less soluble than CaO and Ca(OH) 2 , in accordance to what reported in our previous study and with the results of Morone et al , where Ca concentrations in the eluates decreased of at least one order of magnitude compared to the untreated material.…”
Section: Resultssupporting
confidence: 92%
“…The thin-film route carbonation tests were carried out on BOF slag samples c and d in a pressurized stainless steel reactor placed in a water bath for temperature control. The operating conditions selected for this route based on previous investigations (Baciocchi et al, 2011(Baciocchi et al, , 2015Morone et al, 2014) were a L/S of 0.3 l/kg, a temperature of 50°C, and a total pressure of 7-10 bar. For both types of routes, different reaction times (ranging from 0.5 to 24 h) and CO2 concentrations in the gas flow were tested.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that a number of different types of steel slag present a significant reactivity with CO2, allowing to achieve, for specific process routes and operating conditions, relevant CO2 uptakes (Huijgen et al, 2005;Baciocchi et al, 2010Baciocchi et al, , 2015Uibu et al, 2011;Chang et al, 2012;Santos et al, 2013a,b). Furthermore, several types of residues generated in steel manufacturing plants, such as Basic Oxygen Furnace (BOF), Electric Arc Furnace (EAF), and argon oxygen decarburization (AOD) slag, are typically not valorized and generally landfilled, or employed only for low-end applications, owing for their significant content of free calcium and magnesium (hydr)oxides that may result in poor volumetric stability and hence in a low technical performance in construction applications (Morone et al, 2014). Therefore, accelerated carbonation of these types of materials may also represent a treatment strategy to improve their properties in view of valorization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The production of carbonate-bonded aggregates from Basic Oxygen Furnace (BOF) steel slags was investigated by Morone et al [48] in a lab-scale granulation device and more recently by the same group also in a pilot-scale rotating drum [49]. Operating at lab-scale at 40% CO 2 concentration and ambient temperature and pressure, allowed to obtain a CO 2 uptake of 2.5% immediately at the end of the test (30 min) and of 5.5% after 28 days curing in a moist atmosphere.…”
Section: Figurementioning
confidence: 99%